2015
DOI: 10.3928/01913913-20150602-01
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Ulcerative Keratitis Following Retinopathy of Prematurity Treatment

Abstract: Infectious ulcerative keratitis developed in a small, but significant, percentage of patients undergoing treatment for ROP. Postoperative corneal epithelial defects with subsequent corneal haze appear to be involved in the progression to ulcerative keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…noted corneal epithelial defects in 10 of 110 eyes (9.1%) treated for ROP, with progression to ulcerative keratitis in 4 of 98 (4.08%) of eyes treated with laser. [ 6 ] The authors emphasized the potential of corneal epithelial defects after laser to develop into ulcerative keratitis. [ 6 ] Potential corneal scarring is particularly important in neonates given the potential for deprivation amblyopia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…noted corneal epithelial defects in 10 of 110 eyes (9.1%) treated for ROP, with progression to ulcerative keratitis in 4 of 98 (4.08%) of eyes treated with laser. [ 6 ] The authors emphasized the potential of corneal epithelial defects after laser to develop into ulcerative keratitis. [ 6 ] Potential corneal scarring is particularly important in neonates given the potential for deprivation amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The authors emphasized the potential of corneal epithelial defects after laser to develop into ulcerative keratitis. [ 6 ] Potential corneal scarring is particularly important in neonates given the potential for deprivation amblyopia. Accordingly, it is appropriate to take reasonable steps to reduce the risk of corneal epithelial defects after laser for ROP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods focus on the late stages and do not address the underlying pathological defects. Each has significant safety implications [ 149 ], such as ulcerative keratitis, intravitreous vascular hyperplasia, retinal detachment, and sustained retinal vascularization [ 150 , 151 , 152 , 153 ]. Therefore, it is important to search for safer and more effective treatments.…”
Section: Application Of Scs In Refractory Diseases Of Newbornsmentioning
confidence: 99%
“…Laser photocoagulation was found to cause infectious ulcerative keratitis in a subgroup of ROP infants. The mechanism involved postoperative corneal epithelial defects that led to corneal haze 14. Another study of long-term ophthalmological outcomes in children treated for threshold ROP by indirect laser photocoagulation reported that these patients had higher risks of strabismus, astigmatism, nystagmus, myopia, and lowered visual acuity compared to the control subjects, infants with spontaneously regressed ROP 15…”
Section: Mechanisms and Current Therapies For Ropmentioning
confidence: 99%